Implementasi Strategi Kebijakan Pemerintah Kota Banjar Dalam Upaya Pengendalian Penyakit Mulut Dan Kuku (PMK) Di Kota Banjar - Iis Meilia (Pusat Riset dan Inovasi Nasional, 2023)
Foot and Mouth Disease (FMD) is an old disease that has reappeared. In early 2022, FMD entered Banjar City with a fairly massive attack on beef cattle. Although the mortality rate was low, yet it was very detrimental economically for breeders and livestock businessman. Especially before the feast of sacrifice. In response to these conditions, the government of Banjar City, according to their authority and inseparable from the regulations related to FMD control from the central government, has made various efforts to reduce the number of spreads and take preventive actions. These efforts is carried out with the relevant stakeholders including community participation and breeders. This study aims to describe, know, and portray as well as analyze, and also explain the supporting factors and obstacles in the implementation of the policy strategy implemented by the City of Banjar. This study uses informants as the source of information and data, and documentation so that the,results of the study obtain that communications, resources, dispositions, also bureaucratic structure of the technical implementers and related administrative officials has ran quite well, although it is still based on the existence of incentives. However, for the related implementers stakeholders and public, of the four aspects mentioned, not all as expected, because of sectoral ego reasons or because of a differentscientific backgrounds, so that they make different understandings. The results of the study and analysis show that the implementation of the FMD control policy strategy in the city of Banjar is running according to its objectives.